Expired Chicken Egg-White Extract’s Adsorption Behavior As a Corrosion Inhibitor for Carbon Steel in 1M HCl - Esseddik Elqars; Mohamed Guennoun; Aicha Ouarhach; Noufissa Sqalli Houssini; Mohammed Elhafdi; Abdelhafid Essadki; Mohamed Ait chaoui; Taibi Nbigui (Journal of Chemistry)
The inhibitory activity of the expired egg-white carbon steel (CS) extract in HCl solution was studied in this article. The extract was examined using FT-IR, and the surface was examined using a scanning electron microscope (SEM) and energy-dispersive X-ray analysis (EDX). Weight loss techniques at various temperatures were used to examine corrosion investigations (298, 308, 318, and 328 K), concentrations (100, 200, 400, and 800 mg. L−1) of extracts, and electrochemical measurements (potentiodynamic polarization (PDP) and impedance spectroscopy (EIS) at 25°C and different concentrations. Results. Results obtained through EIS demonstrated a maximal inhibition efficiency of 90% at an inhibitor concentration of 800 mg. L−1. Moreover, the findings of the potentiodynamic polarization indicated that egg-white extract was a mixed type of inhibitor and slowed down both cathodic and anodic reactions. For weight loss analysis, an inhibitory potency (89, 83, 77, and 71%) at various temperatures (298, 308, 318, and 328 K) was demonstrated, respectively. It indicates that the temperature rise contributes to a decrease in the resistance of the carbon steel. The adsorption of the expired egg-white extract was spontaneous with physisorption and chemisorption according to the Langmuir isotherm model, according to adsorption isotherm studies.